PERSPEKTIF KEPUASAN KARYAWAN PT. OSI ELECTRONICS DISPLAYS BATAM (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2014)
Employees, as well as consumers, need to be pampered, cared for, and meet their expectation. Company has some responsibilities that must be met, one of them is corporate social responsibilities for their employess. Company has an effort to fulfil these responsibilities. Companies give a resiprocal return for employee’s energy, idea, and thought that. If the return fulfiled by companied meet employees expectation, it might be made employee satisfied and have a loyality to companies. However, infact, always appears a gap betweem the expectation and point of view and company management. This matter will result in the emergence of turnover. The purpose of this research is to determine the level of employees PT OSI Electrics Displays Batam. The amount of this research is 79 respondents. Tool data collection using questionaires and analysis techniques used are importance and performance analysis. The result showed that the company needs to pay closer attention to variable work it self, because great expectations of employees to get challenging job that can enrich their skills and knowledge as well as fun job.